Interaction of influenza A virus NS2/NEP protein with the amino-terminal part of Nup214 - TURAN, KADİR (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Influenza A viruses have a single-stranded RNA genome consisting of 8 segments. Each RNA segment associates with the nucleoprotein (NP) and viral RNA polymerase to and from a viral ribonucleoprotein (vRNP) particle. The viral mRNA synthesis is dependent on a capped pruner derived from nascent host RNA transcripts. For these processes to take place, vRNPs must pass through the cell nuclear pore complex (NPC) to the nucleus. The influenza A virus NS2 protein, also called the nuclear export protein (NES), has an important role in the nucleocytoplasmic transport of vRNPs. This protein interacts with the host cellular nucleoporins during the nuclear export of vRNPs. In this study, the human nucleoporin 214 (Nup214) was identified as an NS2-binding protein by using a yeast two-hybrid assay. The interaction between NS2 and human Nup214 was confirmed in both yeast and mammalian cells. It has been shown that the NS2 protein interacts with the amino terminal FG domain of the Nup214 protein. The influenza viral replication was suppressed in knockdown cells for the Nup214 protein. It was concluded that the FG domains of nucleoporins have an important role in the interaction of the influenza NS2 protein with host NPC for vRNA export.
Keywords: Influenza A viruses; NS2/NEP; Nup214; nuclear pore complex; nuclear export; NUCLEAR-PORE COMPLEX; NUCLEOCYTOPLASMIC TRANSPORT; FUNCTIONAL-ANALYSIS; NUCLEOPORIN NUP214; EXPORT PROTEIN; M1 PROTEIN; DOMAIN; IMPORT; OVEREXPRESSION; POLYMERASE